Bacterial mutagenicity assays: Vehicle and positive control results from the standard Ames assay, the 6‐ and 24‐well miniaturized plate incorporation assays and the Ames II™ assay. (20th May 2016) - Pant, Kamala; Bruce, Shannon; Sly, Jamie; Klug Laforce, Michelle; Springer, Sandra; Cecil, Mark; Andrus, Edgar; Dakoulas, Emily; Wagner, Valentine O.; Hewitt, Nicola J.; Kulkarni, Rohan
Abstract : Bacterial mutation assays are conducted routinely as part of the safety assessment of new chemicals. The OECD Test Guideline (TG) 471 describes the conduct of the standard agar plate Ames assay, required for regulatory submissions. Higher throughput non‐OECD 471 TG assays, such as the miniaturized plate incorporation and Ames II™ assays, can be used for prescreening purposes. We have compiled historical vehicle and positive control data generated using these methods. The historical database is comprised from experiments spanning 9 years and includes >1000 experiments from the standard Ames assay using the plate incorporation and pre‐incubation methods (TA98, TA100, TA1535, TA1537, and WP2 uvrA ), >50 experiments from the 6‐well (TA98, TA100, TA1535, TA97a, and WP2 uvrA ) and >100 experiments from the 24‐well (TA98, TA100, TA102, TA1535, TA1537, and TA97a) plate incorporation assays, and >1000 experiments from the Ames II™ assay (TA98 and TAMix). Although miniaturization to a 24‐well format made the measurement of control revertant colonies in TA1537 and TA1535 more difficult; this can be overcome by using an alternative strain with a higher spontaneous reversion rate (i.e., using TA97a instead of TA1537) or by increasing the number of replicate wells to 12 (for TA1535). All three miniaturized methods, including the Ames II™ assay, were responsive to known mutagens and the responses were reproducible over years of use. These data demonstrate the excellent reproducibility of the standard and miniaturized bacterial mutation assays using positive control chemicals. Environ. Mol. Mutagen. 57:483–496, 2016. © 2016 Wiley Periodicals, Inc.